Circuit simulation assisting Physical Fault Isolation for effective root cause analysis. (September 2017) - Boostandoost, M.; Gräfje, D.; Pop, F.
Abstract: In this study, the PFI (Physical Fault Isolation) was assisted with the analog circuit simulation to provide insight into the device performance under the failed condition and the failure mechanisms. This approach allows us to choose and apply the right PFI technique to find the failure root cause in a very time effective manner and propose the failure mode hypothesis. Accordingly, as an alternative to the conventional circuit modification approaches a backside PLS (Photoelectric Laser Stimulation) based technique was applied to the suspicious analog block. In this technique, a laser with the wavelength in the NIR (Near Infrared) range stimulates the analog circuit block at the transistor level and changes the device electrical state from fail to pass. Consequently, we could evaluate the circuit behaviour at failed condition and verify the failure. In this manner, the competent combination of PFI and analog circuit simulation successfully leads us to the corrective action to improve the circuit design and overcome the inevitable fabrication process variation.